Acupuncture as Adjuvant Therapy for Sleep Disorders in Parkinson's Disease - Fábio Henrique de Amorim Aroxa; Ihana Thaís Guerra de Oliveira Gondim; Elba Lúcia Wanderley Santos; Maria das Graças Wanderley de Sales Coriolano; Amdore Guescel C. Asano; Nadja Maria Jorge Asano (Medical Association of Pharmacopuncture Institute, 2017)
There are few studies which attest the efficacy of acupuncture on treatment of sleep disturbs in Parkinson disease. The aimed of this randomized clinical trial was to evaluate the effects of acupuncture on sleep disturbs of 22 patients with diagnosis of idiopathic Parkinson disease (Hoehn-Yahr 1 to 3) who have assistance on the Pro-Parkinson Program of Clinical Hospital at Federal University of Pernambuco in Brazil. All participants were evaluated by Parkinson Disease Sleep Scale (PDSS) before and after 8 weeks. The experimental group was submitted to 8 sections (once a week) which had duration of 30 minutes. The control group had no intervention. The intervention was executed using the acupuncture points LR3 (Taichong), SP6 (Sanyinjiao), LI4 (Hegu), TE5 (Wai-Guan), HT7 (Shenmen), PC6 (Neiguan), LI11 (Quchi), GB20 (Fengchi). Paired analyses were obtained by Wilcoxon test and independent analyses were made according to Mann-Whitney test. This study presented a potential therapeutic benefit of acupuncture on sleep disturbs of Parkinson's disease patients. This study showed a possible therapeutic benefit through acupuncture in sleep disorders in patients with PD. However, we propose new studies related to the effects of acupuncture on the clinical symptoms and evolution of the disease.